"Grupo de Asturianos al servicio de un pieza artillera durante el cerco". Series of 4 photos. Copied from CNT collection (1937)
"Grupo de Asturianos al servicio de un pieza artillera durante el cerco". Series of 4 photos. Copied from CNT collection.